Pengembangan Media Pembelajaran Modul dan Jobsheet Pada Trainer Instalasi Penerangan Listrik di SMKN 1 Kramatwatu - Siti Annisa Nindia Larasati; Mohammad Fatkhurrokhman; Siswo Wardoyo (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This research is based on the limited learning media in the electrical lighting installation subject, and the lack of modules and jobsheets to support the use of trainers in practical activities. Therefore, this study aims to produce learning media in the form of modules and jobsheets for the Electrical Lighting Installation subject and to find out the level of eligibility. This research uses the R&D (Research and Development) method with the 4D development model, which includes the define, design, develop, and disseminate stages. The final product of this study is a module and jobsheet for the Electrical Lighting Installation subject. Data were collected through observation, interviews, and questionnaires. The data were analyzed using a Likert scale to measure the feasibility of the product based on evaluations from material experts, media experts, and user responses. The results of the study show that the module and jobsheet learning media that have been developed are very suitable to be used in practical learning. The final step in making the module and jobsheet is a feasibility test by material experts and user responses, tested by lecturers from Sultan Ageng Tirtayasa University, teachers, and several students of SMKN 1 Kramatwatu. After the feasibility test, the results show a feasibility percentage of 92% from users, 84.8% from material experts, and 89.5% from media experts. Based on these results, the module and jobsheet learning media are categorized as very feasible to use.